Assistance in Mastering PCR Methods for Olympiad Students at MAN Insan Cendekia in Kendari City - Syah, Muhamad Azwar; Raharjo, Sapto Raharjo; Jamili; Ambardini, Sri; Jeni; Syahrir; Yamin Yaddi; Munadi, La Ode Muh (Majalah Pengabdian Indonesia, 2025)
Madrasah Aliyah Negeri Insan Cendekia (MAN IC) in Kendari City is one of the OSN (National Science Olympiad) participants in the subject of biology, which is required to understand the idea and practice of PCR (Polymerase Chain Reaction). However, there are insufficient skilled PCR teachers at the school, and no PCR facilities are currently accessible. The goal of this mentoring is to provide an in-depth understanding of the concept of PCR as well as full training on how to use PCR effectively. The method consists of two components: community education and training. The introduction of the PCR concept in this community service includes genetic material, DNA concepts, genes, genomes, DNA isolation, and DNA replication, while the training material includes solution taking techniques, PCR solution preparation, PCR usage procedures, PCR result visualization with electrophoresis, and data interpretation. The PCR has three main steps consisting of denaturation, annealing and extension which are carried out for 30-35 cycles with different temperatures at each step. The evaluation results showed that this mentoring helped the student understand PCR and was beneficial for the OSN competition due to its relevance to the competition syllabus. Moreover, the student also received a bronze medal in the biology competition.